NURSING IN WOMEN’S HEALTH: NURSING IN THE CARE OF PREGNANT WOMEN WITH GESTATIONAL DIABETES - Kamilly Rocha Dantas, Amanda (Health and Society, 2024)
INTRODUCTION: Nursing plays a key role in the care of pregnant women with gestational diabetes, this involves monitoring blood glucose levels closely, providing guidance on diet and exercise, medication if necessary and educating the pregnant woman on managing the condition . Additionally, nurses can also help in preventing complications for the mother and baby by providing support and closely monitoring progress during pregnancy. The exact cause of gestational diabetes is not clear, but there are some hypotheses. Placental hormones help develop and maintain the baby, but they also block the normal action of insulin in the mother’s body during pregnancy. The nurse discovers gestational diabetes during prenatal care, he works with educational measures and support groups, advises the pregnant woman to attend for glycemic control and takes her to a medical consultation and with a nutritionist to avoid problems during pregnancy. OBJECTIVE: Identify the main importance in caring for women with gestational diabetes. METHODOLOGY: This is an integrative review of the literature, data collection was carried out between August and April 2023 and 2024. The descriptors used for the search were: Nursing, Diabetes, Gestational Diabetes, Nursing Care with GDM . FINAL CONSIDERATIONS: To ensure that pregnant women with diabetes receive adequate treatment, keep the disease under control and enjoy a good quality of life, nurses have the important role of creating strategies that motivate them to follow the treatment, make changes in their lifestyle necessary lifestyle, educate them about the condition and promote self-care.